2014
DOI: 10.1039/c3nr05048c
|View full text |Cite
|
Sign up to set email alerts
|

Small nickel nanoparticle arrays from long chain imidazolium ionic liquids

Abstract: A series of six long chain alkyl mono- and bi-cationic imidazolium based salts with bis(trifluoromethylsulfonyl)imide (NTf2(-)) as the anion were synthesized and characterized. The single crystal structure of 1-methyl-3-octadecylimidazolium bis(trifluoromethylsulfonyl)imide could be obtained by X-ray analysis. All these long chain alkyl imidazolium based ILs were applied in the synthesis of nickel nanoparticles via chemical decomposition of an organometallic precursor of nickel. In these media, spontaneous dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…Work by others has shown that decomposition of [Ni(COD) 2 ] in 1‐alkyl‐3‐methyl‐imidazolium ILs with different alkyl chain lengths and the bis(trifluoromethylsulfonyl)imide anion gave Ni NPs with an average diameter of 2.4–5.4 nm or 4.9–5.9 nm …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work by others has shown that decomposition of [Ni(COD) 2 ] in 1‐alkyl‐3‐methyl‐imidazolium ILs with different alkyl chain lengths and the bis(trifluoromethylsulfonyl)imide anion gave Ni NPs with an average diameter of 2.4–5.4 nm or 4.9–5.9 nm …”
Section: Resultsmentioning
confidence: 99%
“…Work by others has shown that decomposition of [Ni(COD) 2 ] in 1-alkyl-3-methyl-imidazolium ILs with different alkyl chain lengths and the bis(trifluoromethylsulfonyl)imide anion gave Ni NPs with an average diameter of 2.4-5.4 nm [49] or 4.9-5.9 nm. [16] Prechtl [50] Ac ombined TEM and energy dispersive X-ray spectroscopic analysis( EDX, Figure4)s hows only the expected nickel emission lines.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the T g values of phosphonyl-based ionic liquids with T m of corresponding all-carbon reference ionic liquids containing the same number of side-chain carbons, shows the dramatic impact of the presence of phosphonate functionality upon the phase transition temperatures of the ionic liquids, which demonstrably decreases the T g values of new TSILs. For instance, [C 12 C 1 im][NTf 2 ] comprising a saturated C 12 side chain, has a T m value of 34.9 o C reported by Mudring et al; 9 however, replacement with a phosphonyl unit (IL 11) yields T g of -24.0 o C and converts a crystalline solid to an amorphous liquid. It is reasonable to assume that the introduction of phosphonyl functional group lowered the tendency for crystallization.…”
Section: Resultsmentioning
confidence: 96%
“…The properties of the alkyl chains also had a strong impact on the size of Ni nanoparticles prepared from Ni(COD) 2 in imidazolium ionic liquids [36,66,67]. Interestingly, Prechtl, Santini, Dupont and co-workers achieved the roomtemperature synthesis of Ni nanoparticles via the auto-decomposition of Ni (COD) 2 (Fig.…”
Section: Size Control Via the Il Cationmentioning
confidence: 94%